"Capturing" sound - Lechleitner, Gerda (Traditiones (Ljubljana), 2005)
Even though folk music collections rich in written documents had existed for along time, it was the invention of sound recording that - from today's point of view - marked the "real" beginnings of folk music research and added an entirely new aspect to the discipline. However, although the use of a recording machine was undisputed in the field of ethnomusicology - and indeed a prerequisite, as stated in the motion to establish the avienna Audiovisual Research Archive - some folk music researchers had serious doubts whether suchan apparatus would be necessary at all, fearing that it might "destroy" the music recorded and render it "lifeless". Today, after 100 years of sound recording, we must distinguish between speech (real sound) and writing, between commercial and recordings, different needs. This paper deals with the change in folk music research since the very first recordings, the influence and acceptance of the new technology, and aspects of the historical framework.
Keywords: etnomuzikologija; metodologija; folk music; ljudska glasba; snemanje; fonografi; zgodovinski pregledi